Rapid Development of Bleeding Esophageal Varices after Placement of Continuous Flow Left Ventricular Assist Device. (6th November 2019) - Majmudar, Kaushal; Northcutt, Michael; Gordon, Robert; Fimmel, Claus J.
Abstract : We describe a patient with compensated cirrhosis and portal hypertension who underwent continuous flow LVAD implantation. Shortly after LVAD implantation, the patient developed new onset bleeding esophageal varices and ultimately had a fatal outcome. Our experience suggests that even well-compensated cirrhotic patients with significant portal hypertension are at risk of variceal bleeding after LVAD placement.